Rheumatologists' Acceptance of Patient Referrals from Physical Therapists - Feldman, Debbie Ehrmann (Healthc Policy, 2020)
We surveyed Canadian rheumatologists regarding beliefs about physical therapists' (PTs) ability to refer patients appropriately to rheumatologists and whether they would accept such referrals. Most (86.9%) believed that PTs can appropriately refer to rheumatologists. However, only 48.2% of rheumatologists would be very or extremely likely to accept a referral from a PT they knew, and 23.5% would accept a referral from a PT they did not know. Conversely, 90.5% would accept a referral from a PT if they could bill it as a full consult. We conclude that being able to bill PT referrals as full consults may potentially enhance the acceptance of PT referrals.